1987
DOI: 10.2307/2008249
|View full text |Cite
|
Sign up to set email alerts
|

Steady State Computations for Wave Propagation Problems

Abstract: Abstract. The behavior of difference approximations of hyperbolic partial differential equations as time t -* oo is studied. The rate of convergence to steady state is analyzed theoretically and expe ¡mentally for the advection equation and the linearized Euler equations. The choice of difference formulas and boundary conditions strongly influences the rate of convergence in practical steady state calculations. In particular it is shown that upwind difference methods and characteristic boundary conditions have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…It follows from (48), (49) and the correlation coefficients in (50) and (51) that the contribution to the decay of the variance depends on the correlation between the characteristic variables at the boundaries. A negative correlation lowers the variance and a positive correlation increases the variance.…”
Section: Decaying Variance On the Boundarymentioning
confidence: 99%
See 1 more Smart Citation
“…It follows from (48), (49) and the correlation coefficients in (50) and (51) that the contribution to the decay of the variance depends on the correlation between the characteristic variables at the boundaries. A negative correlation lowers the variance and a positive correlation increases the variance.…”
Section: Decaying Variance On the Boundarymentioning
confidence: 99%
“…Figure 3 and 4 shows the variance decay with time comparing characteristic and non-characteristic boundary conditions when using a normally (ξ ∼ N (0, 1)) and uniformly distributed (ξ ∼ U(− √ 3, √ 3)) ξ respectively. Note the similarity between studying variance decay in the case of zero variance on the boundary and analyzing convergence to steady state, see [49,50,51].…”
Section: Zero Variance On the Boundarymentioning
confidence: 99%
“…In this section, normal mode analysis [17] is used to estimate the convergence rate to steady state for different sets of open boundary conditions for the INS equations. This procedure has been used in several studies, see for example [28,7], and the results in this section are found in Article III. A similar procedure is also used in Article I for the compressible Euler equations and Article II for the spatial operator of the INS equations.…”
Section: Spectral Analysismentioning
confidence: 99%
“…The solution to the whole system (23) becomes φ = (0, 0, 0, 0) and ψ = σ 3 ψ 3 + σ 4 ψ 4 , where ψ 3 = (− √ γ − 1, 0, 0, 1) and ψ 4 = (0, iωū, s, 0) . Finally, the homogeneous solution to (20) is Ŵh = ΨK(x) σ, where Ψ = [ψ 1 , ψ 2 , ψ 3 , ψ 4 ], K(x) = diag(e κ 1 , e κ 2 , e κ 3 , e κ 3 ) and σ = (σ 1 , σ 2 , σ 3 , σ 4 ) contain the solution vectors, the exponential functions and the parameters that will be determined from the boundary conditions, respectively.…”
Section: The Spectrummentioning
confidence: 99%